2023
DOI: 10.3389/fonc.2022.1078315
|View full text |Cite|
|
Sign up to set email alerts
|

Application of a multispecies probiotic reduces gastro-intestinal discomfort and induces microbial changes after colonoscopy

Abstract: Even after decades of research and pharmaceutical development, cancer is still one of the most common causes of death in the western population and the management of cancer will remain a major challenge of medical research. One of the most common types of cancer is colorectal cancer (CRC). Prevention by detection of early-stage precursors is the most reliable method to prevent CRC development. In dependence of age, familial predisposition, and other risk factors the preventative routine screening for CRC by co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A total of six included studies [19,[21][22][23][26][27] in the quantitative synthesis showed numerous results in before and after-colonoscopy groups, as shown in Table 2.A and 2.B, respectively. Souza et al [23] reported a statistically significant reduction in abdominal pain symptoms in before colonoscopy probiotics groups (p=0.032).…”
Section: Final Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of six included studies [19,[21][22][23][26][27] in the quantitative synthesis showed numerous results in before and after-colonoscopy groups, as shown in Table 2.A and 2.B, respectively. Souza et al [23] reported a statistically significant reduction in abdominal pain symptoms in before colonoscopy probiotics groups (p=0.032).…”
Section: Final Resultsmentioning
confidence: 99%
“…The inclusion criteria were met by a total of 10 studies, including six on probiotics after colonoscopy [20,[23][24][25][26][27] three on probiotics before colonoscopy [19,[21][22], and one that assessed probiotics use in both conditions [12]. The participants included a total of 341 patients receiving probiotics before colonoscopy and 340 in the placebo groups.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations